THE SAILOR OF THE COLLEGE AND THE RADICALIZATION OF THE "POPULATION" OF REEF IN BRIGA BY THE LABOR MARKET. - Bruno Augusto Dornelas Câmara (Clio: Revista de Pesquisa Histórica, 2005)
At the end of June 1848, a confused fight between a Brazilian student and a Portuguese clerk provoked a great wave of violence in Recife. There were looting, a lot of banging and at least five fatalities. At the end of the conflict, a crowd marched until the Provincial Assembly demanding the nationalization of the retail trade and the expulsion of the unmarried Portuguese, within a period of 15 days. The college seamen, as this riot was known, is our gateway to understand the disputes between nationals (free and poor freedmen) and foreigners (small tradesmen and clerks of scarce resources) by the retail trade of the city and the opportunities employment in these establishments. The present article aims to focus on anti - popularism in the popular classes and the relationship between the "popular" politics of the Praieiro Party.